2021
DOI: 10.35860/iarej.859423
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effects of different refrigerants used in the refrigeration system on compressor vibrations and noise

Abstract: Vibration and noise are undesirable effects in daily life and energy-consuming systems. In this study, the effects of different refrigerants on noise and vibration in a sealed reciprocating compressor are discussed. The study compared the noise and vibration performances of refrigerants with lower ozone depletion potential (ODP) values compared to R22, which has a high ODP value. The study was carried out experimentally in two stages. Firstly, tests were conducted for the coefficient of performance (COP) of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Both substitute gases of R-404A have better COP than this (2.28 w/w (COP/EER)) [21]. Moreover, Cingiz et al [22] found that there is a correlation between the COP and noise and vibration of the refrigerant gases. The higher the COP value, the lower the noise values.…”
Section: Discussionmentioning
confidence: 98%
“…Both substitute gases of R-404A have better COP than this (2.28 w/w (COP/EER)) [21]. Moreover, Cingiz et al [22] found that there is a correlation between the COP and noise and vibration of the refrigerant gases. The higher the COP value, the lower the noise values.…”
Section: Discussionmentioning
confidence: 98%
“…Ev tipi ve ticari tip soğutma cihazları için soğutma işleminde, genleşme cihazı olarak bir kılcal boru veya termostatik genleşme valfinin kullanıldığı buhar sıkıştırmalı soğutma çevrimi tercih edilmektedir. Yoğunlaştırıcı ve buharlaştırıcı içindeki soğutucu akışkanın faz değişimini gerektiren buhar sıkıştırmalı soğutma sistemidir [19]. Deneysel sistem, buhar sıkıştırmalı soğutma çevrimi esasına göre dizayn edilmiştir.…”
Section: A Materyalunclassified